2019
DOI: 10.1016/j.proci.2018.05.061
|View full text |Cite
|
Sign up to set email alerts
|

A three-equation model for the prediction of soot emissions in LES of gas turbines

Abstract: The design of new low-emission systems requires the development of models providing an accurate prediction of soot production for a small computational cost. In this work, a three-equation model is developed based on mono-disperse closure of the source terms from a sectional method. In addition, a post-processing technique to estimate the particles size distribution (PSD) from global quantities is proposed by combining Pareto and log-normal distributions. After validation, the developed strategy is used to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Nonetheless, both LES-CMC and ISRN methods show very promising potential in capturing soot location even with a simplified soot model. These methods are comparable with approaches of other researchers using different turbulent combustion closure methods with more advanced soot models [4,[28][29][30][31]. In terms of magnitude, however, both simulations over-predict the total soot volume fraction, as also observed with other studies using semi-empirical two-equation soot models [32,33] in this burner.…”
Section: Resultssupporting
confidence: 86%
“…Nonetheless, both LES-CMC and ISRN methods show very promising potential in capturing soot location even with a simplified soot model. These methods are comparable with approaches of other researchers using different turbulent combustion closure methods with more advanced soot models [4,[28][29][30][31]. In terms of magnitude, however, both simulations over-predict the total soot volume fraction, as also observed with other studies using semi-empirical two-equation soot models [32,33] in this burner.…”
Section: Resultssupporting
confidence: 86%
“…Background and comprehensive reviews on these subjects may be found in Ramkrishna (2000); Fox (2003); Marchisio & Fox (2007) and references therein. Along these lines, a large variety of numerical approaches have been discussed in the literature to simulate crystallisation in liquid (Qamar et al, 2007), carbon and soot formation in flames (Leung et al, 1991;Balthasar & Kraft, 2003;Ma et al, 2005;Lindstedt & Louloudi, 2005;Zucca et al, 2006;Patterson & Kraft, 2007;Eberle et al, 2017;Sewerin & Rigopoulos, 2017;Rodrigues et al, 2018;Aubagnac-Karkar et al, 2018;Schiener & Lindstedt, 2019;Franzelli et al, 2019) and many other chemical engineering applications with noninertial particles. Works have focused on numerical methods for the direct solving of the particle size distribution after discretisation of the phenomena driving its time evolution (Gelbard & Seinfeld, 1978;Hounslow et al, 1988;Lister et al, 1995;Kumar & Ramkrishna, 1996a,b, 1997Rigopoulos & Jones, 2003;Filbet & Laurenot, 2004;Park & Rogak, 2004;Qamar et al, 2007;Nguyen et al, 2016;Sewerin & Rigopoulos, 2017), while others adress the problems from moments of the distribution (Frenklach, 2002;Mueller et al, 2009;Salenbauch et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Neural networks for solving population balance equation bustion systems. [17][18][19] To progress in this direction, this paper reports an attempt in which the effort made in grid size resolution and precision of PSD solving, serves to train a set of neural networks for solving the population balance equation. Neural networks are subsequently coupled with the flow solution, thus allowing for a significant reduction of the computing cost, still preserving the accuracy provided by the numerical method generating the training database.…”
Section: Please Cite This Article As Doi:101063/50031144mentioning
confidence: 99%